Determination of pKa for some Schiff bases derived from benzaldehyde and amino phenols by conductivity measurement - M. M. Gh. A. E. AL-Dabbagh (College of Education for Pure Sciences, 2014)
The aim of this  work is concerned with the determination of pka for some Schiff bases by conductivity method.These imines are prepared by reactions of benzaldehyde with o,m,p-amino phenols by standard method. The structures of these imines are confirmed by using some physical methods, namely, U.V,I.R and melting points. Experimentally it is observed,that intramolecular hydrogen bonding may contribute in decreasing pka value of benzylidene-o-hydroxyaniline. The presence of phenolic groups at m and p-positions of primary amine side of the Schiff bases, have a noticeable influence on the collected  pka values. The thermodynamic of ionization reactions of these Schiff bases are determined. These showed a positive sign values of  ΔG˚ and ΔH˚ thermodynamic parameters. Also ΔS˚ value has a negative sign. These positive and negative signs values are discussed in detail.